Pengaruh Tingkat Kemiskinan Terhadap Pertumbuhan Ekonomi Di Provinsi Di Sumatera Selatan Periode 2013 – 2023 - Cempaka Lestari; Iza Tulah Anisa; Peny Cahaya Azwari (Universitas Sahid Surakarta, 2024)
ABSTRACT Economic growth is the main requirement for reducing poverty levels. The goal of economic growth has an active influence on poverty, because increased economic growth results in the emergence of jobs thereby reducing unemployment which causes poverty levels to increase. One measure of economic growth can be assessed from the level of income in the area. Therefore, the aim of this research is to determine the effect of poverty on economic growth in South Sumatra in 2013-2023. The analytical tool used in this research is a panel data regression model sourced from the BPS. This research uses simple linear regression in the statistical application of the SPSS ML program. This test was carried out to determine the relationship between poverty and economic growth in South Sumatra Province in 2013-2023. The results and research carried out showed that the influence of the poverty variable was negative and not significant on variable Y (economic growth).